Can the green credit policy promote green innovation in enterprises? Empirical evidence from China - Fang, Xubing; Liu, Maotao; Li, Guangqin (Technological and Economic Development of Economy, 2024)
The green credit policy (GCP) is an institutional framework aimed at guiding enterprises towards green transformation and promoting high-quality development, which serves as a crucial tool for supporting the establishment of a green technology innovation system. In this study, utilizing the green credit guidelines as a quasi-natural experiment and constructed a continuous difference-in-difference (DID) model, examines the impact of GCP impact on enterprise green innovation and its internal mechanisms by analyzing data from Chinese A-share listed companies between 2006 and 2021. Our findings indicate that the GCP had a significant impact on enterprise green innovation, inhibiting companies from in-dependently developing green innovation while promoting joint green innovation with other institutions; These results were robust and consistent, even after conducting several sensitiv-ity analyses; This mechanism indicate that the commercial credit plays an important regulatory role in the process of GCP affecting green innovation of enterprises and the financing constraints act as an intermediary factor in the process of GCP affecting green innovation. Based on our research, we offer policy recommendations aimed at improving the GCP and fostering a market-oriented green technology innovation system.First published online 14 March 2024